(untitled) (Вісник: Міжнародні відносини, 2021)
CSR is defined as the philosophy of behavior and the concept of building a business community, companies, individual business representatives focusing on such orientations as the production of quality products and services, the creation of attractive jobs, the payment of legal wages and investment in the development of human potential, compliance with the requirements of the legislation, labor, environmental, etc., building trusting relationships with all stakeholders, efficient business management, focused on creating added economic value and the growth of the well-being of its shareholders, taking into account public expectations and generally accepted ethical standards in case management, contributing to the formation of civil society through partnership programs and local community development projects. At the same time, regional and national peculiarities of CSR formation, regulation and implementation in the EU are revealed.